The Influence of Religious and Cultural Literacy on Early Marriage Tendencies and Contribution to Achieving the SDGs - Yogi Sopian Haris; Djamaluddin Perawironegoro; Betty Mauli Rosa Bustam; Abdul Gafur Arifin (Profetika: Jurnal Studi Islam, 2025)
Objectives: This study aims to analyze the influence of religious and cultural literacy on the tendency toward early marriage among students at public high schools in Central Lombok. Theoretical framework: This research refers to the Theory of Planned Behavior (TPB) and the concepts of religious literacy as proposed by Stephen Prothero and Diane L. Moore, cultural literacy as formulated by E. D. Hirsch, as well as early marriage as defined by UNICEF and BKKBN. These concepts are positioned as conceptual–theoretical frameworks for analyzing early marriage tendencies. Literature review: Previous studies have shown that early marriage is generally caused by many factors, including misinterpretation of religious teachings, cultural norms that support young marriage, economic pressure, and a lack of social control and reproductive awareness. However, little research has specifically reviewed the influence of religious and cultural literacy in that context. Method: This research uses a quantitative approach with an associative kind, 373 respondents selected using the cluster area sampling technique with a two-stage cluster. The data was analyzed using correlation analysis and simple linear regression. Result: The findings show that religious literacy significantly affects the tendency toward early marriage, with a contribution of 24.2% (Y = 68.729 – 0.460X₁), while cultural literacy contributes 26% (Y = 67.277 – 0.448X₂). The multiple regression equation Y = 71.896 – 0.237X₁ – 0.283X₂ indicates that both religious and cultural literacy together explain 28.9% of the variation in early marriage tendencies. A negative correlation (r = -0.492 and r = 0.510) demonstrates that the higher the religious and cultural literacy, the lower the tendency toward early marriage. These findings emphasize that strengthening literacy in both domains effectively reduces early marriage rates by fostering critical understanding of religious teachings, constructive interpretation of cultural values, and rational decision-making among adolescents. Implications: This finding confirms the importance of integrating religious and cultural values education into the school curriculum and local policies to support the achievement of the SDGs (goals 3, 4, 5, and 8). Novelty: The novelty of this research lies in its focus on analyzing the influence of religious and cultural literacy, variables rarely studied in the context of the religious and cultural community of Central Lombok, and its relationship to the SDGs. This makes the results significant not only locally but also globally.